2005
DOI: 10.2298/psi0501055c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Big Five model in Serbian culture by FIBI questionnaire

Abstract: The main purpose of this study was to evaluate personality dimensions, proposed by Big Five model, in our culture, by the use of the questionnaire FIBI, developed on the basis of the psycho lexical study of personality descriptions in Serbian language (Smederevac, 2000). There were 627 subjects in the study (407 females and 220 males), aged 17 to 77, and the inventory UKL7 (Smederevac, 2000) and the Big Five Inventory (BFI; John, Donahue, Kentle, 1991; John, Srivastava, 1999) were applied. The FIBI inventory w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The authors of the inventory have declared it free to use for noncommercial purposes. The Serbian/Croatian version of the inventory, which was used in this study is the version which was previously used in a number of studies in Serbia [11][12][13][14] . Stojanović 15 conducted a study on a sample of 304 participants from Serbia, which demonstrated convergence of BFI measures to analogues personality trait measures obtained by using NEO Personality Inventory -Revised (NEO PI-R).…”
Section: Methodsmentioning
confidence: 99%
“…The authors of the inventory have declared it free to use for noncommercial purposes. The Serbian/Croatian version of the inventory, which was used in this study is the version which was previously used in a number of studies in Serbia [11][12][13][14] . Stojanović 15 conducted a study on a sample of 304 participants from Serbia, which demonstrated convergence of BFI measures to analogues personality trait measures obtained by using NEO Personality Inventory -Revised (NEO PI-R).…”
Section: Methodsmentioning
confidence: 99%
“…This approach has highlighted the importance of evaluative terms, which constitute two personality dimensionspositive valence and negative valence. Out of three psycholexical studies in the Serbian language, two have applied Tellegen and Waller's methodology, yielding results comparable to Big Seven dimensions (Čolović et al, 2014;Smederevac et al, 2007) but also hinted at the possibility of Big Five replication (Colovic et al, 2005). The third study, utilizing word categories, has demonstrated that the trait descriptor structures change according to the word categories included; dispositional terms result in dimensions similar to the Big Five, while the introduction of evaluative terms leads to solutions comparable to the Big Six or HEXACO (De Raad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%